The Study of Accounting Practices in The Uang Panai Tradition (Ethnographic Studies on Traditional Marriages in West Sulawesi) - Nahdhiyah, Nanda; Ayu Damayanti, Ratna; Nirwana, Nirwana (Green Publisher Indonesia, 2022)
Pricing is not only oriented towards material profit, but also oriented to non-material values, such as cultural aspects. This study aims to reveal the accounting practices of Mandar culture in Majene, West Sulawesi, based on an ethnographic review of the meaning of Uang Panai for local communities and accounting practices in setting the price of Uang Panai. This study uses a qualitative approach with an interpretive paradigm. Data collection was done naturally through participatory observation, in-depth interviews, and referring to the literature and previous research results. The data analysis technique uses a modified and simplified Spradley model without reducing and replacing the results of data analysis. The results of the study indicate that the determination of the price of Uang Panai in Mandar Majene is carried out to cover the costs of the wedding party. The process of determining the price of the panai money is carried out in four stages, namely messiq, negotiation, proposal, and mattandajari. The amount of panai can be influenced by the social status of the bride, such as occupation, education, and family power or authority. The price fixing process refers to conventional accounting theory, the concept of price fixers and price takers, and bargaining as in a perfectly competitive market. The results of this study can be used as a reference material for multi-paradigm Accounting learning. In addition, the community gains additional understanding that the amount of panai money depends on the agreement of the prospective bride's family.